Performance of 2–3.6 GHz Five-Port/Three-Phase Demodulators with Baseband Analog I/Q Regeneration Circuit in Direct-Conversion Receivers - Kaissoine Abdou; Antoine Khy; Kais Mabrouk; Bernard Huyart (Journal of Electrical and Computer Engineering)
A comparison between performance of a five-port demodulator (FPD) and a three-phase demodulator (TPD) with both architectures connected to a so-called baseband I/Q regeneration circuit is carried out. In order to compare these two receivers to a classical architecture, the performance of an I/Q demodulator (IQD) is also presented. Measured results show the superiority of TPD and IQD over FPD in terms of residual DC offsets and 2nd order intermodulation distortion (IMD2) products, noise figure (NF), and sensitivity due to the use of active balanced mixers instead of diode power detectors. Lastly, demodulation of three noncontiguous RF carriers shows the stronger potential of the three-phase demodulator (TPD) for applications in future long term evolution-advanced (LTE-A) receivers through EVM and constellation diagram measurements.